The influence of perceived usefulness, perceived ease of use, and financial literacy on interest in using digital banking among students at Sebelas Maret University, Surakarta - Andarias Vanissaputri; Khresna Bayu Sangka (Universitas Nusa Cendana, 2026)
This study examines the influence of perceived usefulness, perceived ease of use, and financial literacy on students’ intention to use digital banking services at Sebelas Maret University. As digital financial services continue to expand, understanding the factors that encourage technology adoption among young consumers has become increasingly important for financial institutions and policymakers. Through a quantitative descriptive approach, primary data was gathered using online questionnaires administered to a student sample selected via purposive sampling. Instrument validity and reliability were assessed using Pearson’s validity test and Cronbach’s Alpha, while data analysis included classical assumption tests and multiple linear regression analysis. The findings reveal that perceived usefulness, perceived ease of use, and financial literacy each exert a positive and significant influence on students’ intention to use digital banking services. Students are more likely to adopt digital banking when they perceive the technology as beneficial, easy to operate, and supported by adequate financial knowledge. These results highlight the importance of user-friendly digital banking platforms and financial literacy development in fostering technology acceptance among younger generations. The study contributes to the literature on financial technology adoption and digital consumer behaviour by providing empirical evidence on the determinants of digital banking acceptance within the higher education context in Indonesia. Keywords: Perceived Usefulness; Perceived Ease of Use; Financial Literacy; Interest In Using Digital Banking